2013
DOI: 10.2337/dc12-1632
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Healthy Eating for People With Diabetes in a Low-Income, Minority Neighborhood

Abstract: OBJECTIVEThis study used qualitative interviews with black and Latino participants with diabetes to further understanding about types of foods eaten, food preparation, sources of foods and meals, communication with providers, and effects of race and ethnicity on eating in this population.RESEARCH DESIGN AND METHODSResearchers recruited black and Latino adults from East Harlem, New York, to participate in four English and Spanish focus groups. Discussions were transcribed, coded, and analyzed to uncover prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 22 publications
1
74
0
Order By: Relevance
“…In our study, eating problems and negative appraisal of diabetes were identified as predictors of diet barriers of patients with type 2 diabetes. Frequent eating problems predict increasing diet barriers, which has also been reported in previous findings (Breland, McAndrew, Gross, Leventhal, & Horowitz, ; Halali et al, ). Food selection and overeating, as well as diet decision‐making, influence diabetes self‐management, particularly in meal planning and preparation (Wansink, ).…”
Section: Discussionsupporting
confidence: 83%
“…In our study, eating problems and negative appraisal of diabetes were identified as predictors of diet barriers of patients with type 2 diabetes. Frequent eating problems predict increasing diet barriers, which has also been reported in previous findings (Breland, McAndrew, Gross, Leventhal, & Horowitz, ; Halali et al, ). Food selection and overeating, as well as diet decision‐making, influence diabetes self‐management, particularly in meal planning and preparation (Wansink, ).…”
Section: Discussionsupporting
confidence: 83%
“…While some of the Black men recognized that managing stress is important to the prevention and management of t2dm, there was also a notable amount of fatalism. Some men felt that there was little that they could to do to prevent or manage the disease, a sentiment that has been identified in other published studies (Breland et al, 2013). Clearly, interventions that are tailored for Black men should educate them on the realities of the illness; t2dm is a chronic disease that can be prevented or managed through intensive lifestyle changes involving both diet and exercise (Norris et al, 2001;Orchard et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The Sociocognitive Model asserts that self-efficacy, which could be enhanced by knowledge and decision-making skills, can predict patients' commitment and persistence in carrying out the targeted behaviors, especially in the face of barriers (Bandura 1977). Those who perceive higher levels of self-management barriers are more likely to exhibit an undermined self-efficacy (Breland et al 2013;Mansyur et al 2013). However, the theoretically meaningful mechanisms underlying the association between the two variables have not yet been established.…”
Section: Background and Significancementioning
confidence: 99%